2018
DOI: 10.5194/acp-18-357-2018
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of organic and inorganic aerosol systems and the effect on gas–particle partitioning in the southeastern US

Abstract: Several models were used to describe the partitioning of ammonia, water, and organic compounds between the gas and particle phases for conditions in the southeastern US during summer 2013. Existing equilibrium models and frameworks were found to be sufficient, although additional improvements in terms of estimating pure-species vapor pressures are needed. Thermodynamic model predictions were consistent, to first order, with a molar ratio of ammonium to sulfate of approximately 1.6 to 1.8 (ratio of ammonium to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
120
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(128 citation statements)
references
References 70 publications
(90 reference statements)
8
120
0
Order By: Relevance
“…S2 and S3 for this study; similar results are found in other studies (Gao et al, 2016;Gao et al, 2017a;Nah et al, 2018). Pye et al (2018) found only minor difference in predicted ammonia partition when an organic phase was considered. It is also assumed that the particles were internally mixed, and that pH did not vary 30 with size.…”
Section: Thermodynamic Modelingmentioning
confidence: 86%
“…S2 and S3 for this study; similar results are found in other studies (Gao et al, 2016;Gao et al, 2017a;Nah et al, 2018). Pye et al (2018) found only minor difference in predicted ammonia partition when an organic phase was considered. It is also assumed that the particles were internally mixed, and that pH did not vary 30 with size.…”
Section: Thermodynamic Modelingmentioning
confidence: 86%
“…One such assumption is that H + accounts for the charge deficit between the watersoluble species present in particles that can be readily measured with an ion chromatograph. This typically includes five cation (NH + 4 , Na + , Ca 2+ , Mg 2+ , and K + ) and three anion (Cl − , NO − 3 , and SO 2− 4 ) species (e.g., Quinn et al, 2006;Sun et al, 1998), though it occasionally includes a limited group of organic anions (Kerminen et al, 2001). A similar definition has also been applied to the nonrefractory inorganic species measured with an Aerodyne Aerosol Mass Spectrometer (NH + 4 , NO − 3 , SO 2− 4 , and partial Cl − ) (Zhang et al, 2005;Quinn et al, 2006).…”
Section: Proxies Based On Electroneutralitymentioning
confidence: 99%
“…This typically includes five cation (NH + 4 , Na + , Ca 2+ , Mg 2+ , and K + ) and three anion (Cl − , NO − 3 , and SO 2− 4 ) species (e.g., Quinn et al, 2006;Sun et al, 1998), though it occasionally includes a limited group of organic anions (Kerminen et al, 2001). A similar definition has also been applied to the nonrefractory inorganic species measured with an Aerodyne Aerosol Mass Spectrometer (NH + 4 , NO − 3 , SO 2− 4 , and partial Cl − ) (Zhang et al, 2005;Quinn et al, 2006). If the aerosol is near neutral (pH ≈ 7) or acidity is dictated by components other than the inorganic ions in the balance (e.g., organic acids), then charge balance will not provide meaningful information (Trebs et al, 2005;Lawrence and Koutrakis, 1996).…”
Section: Proxies Based On Electroneutralitymentioning
confidence: 99%
“…Couvidat et al, 2012;Couvidat and Seigneur, 2011;Paulot et al, 2009;Pun et al, 2006b;Surratt et al, 2010), the oligomerization of SVOC in both organic and aqueous phase (e.g. Aksoyoglu et al, 2011;Couvidat et al, 2012;Denkenberger et al, 2007;Dommen et al, 2006;Kalberer et al, 2006;Lemaire et al, 2016;Trump and Donahue, 2014), the non-ideal behaviour of the organic aerosol (Couvidat et 5 al., 2012, Couvidat andSartelet, 2015;Pun et al, 2006;Pye et al, 2018) or the effect of the aerosol viscosity (Couvidat and Sartelet, 2015;Shiraiwa et al, 2013). However, most CTMs still fall short to reproduce SOA concentration with up to date parameterizations (e.g.…”
Section: Introductionmentioning
confidence: 99%